PROMOTING ENVIRONMENTAL EDUCATION IN MALAYSIAN PRESCHOOLS - Im, Tan Cheng; King, Ewe Mee; Othman, Abdul Razak (Southeast Asia Early Childhood Journal, 2014)
In preserving environment, the Malaysian society might have reached the nominal and functional level but still has a long way to reach the operational stage. Thus it is necessary to change people’s ecological, economic and social perceptions concerning the environment. Environmental education based on life experiences should begin during the very early years of life. Such experiences play a critical role in shaping life-long attitudes, values, and patterns of behavior toward natural environments. Preschool is part of Malaysia's education system. In order to enrich the student’s potential in all aspects of development; inculcate the spirit of love for the environment; instill awareness about the importance of environmental stewardship through fun activities; and fostering feelings of responsibility to protect nature among the children from their early stage of life; promoting environmental education in Malaysian preschools is deemed necessary.